Effectiveness of mindfulness: The evaluation using machine learning algorithm - Krishnamurthy Ramasubramanian; Venkateswarlu Lendale; Gillala Rekha; Kalambur Swaminathan Lavanya (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2022)
Mindfulness is a practice that is thousands of years old. This practice is also included in the modern mindfulness-based stress reduction training, and its effects on our cognitive system are supported by extensive literature that comprehend mostly fMRI studies and task-oriented experiments with control groups. In this paper, the problem of testing the effects of mindfulness therapy, with specific regard to the yoga practice, is addressed with a Network-Oriented Modelling approach. The first component of the proposed network simulates the elicitation of an extreme stressful emotion due to a strong stress-inducing event. This was done following the same line of previous papers that proposed simulations of similar processes. A second component represents the role of memory, attention, and self-awareness in coping with the stressful event. Finally, the yoga practice, divided into physical movements and breathing, is modelled, to show its influence on memory, attention, and self-awareness, leading in this way to a reduction of the stress level.